Pilot Study of Nursing Studentsâ€™ Knowledge towards Genetic Topics - Erawati, Meira; Kusumaningrum, Niken S D (Nurse Media Journal of Nursing, 2015)
Backgrounds: Nowadays, the science of genetics in Indonesia has not touched the world of nursing education and practice in health care. As the first step in order to introduce genetics topic into nursing education, an assessment is needed to identify studentâ€™s knowledge and comfort toward genetics topic.Purpose: The aim of this pilot study was to identify nursing studentsâ€™ knowledge about genetics.Methods: Research design used in this pilot study was descriptive with cross-sectional approach. The survey was conducted using a questionnaire that adopted and adapted from â€œThe Genetic Needs Assessment Surveyâ€ developed by Maradique et.al. This questionnaire was distributed to nursing students at one state school of nursing in Central Java, Indonesia.Result: There were 170 nursing students participated in the pilot study. Descriptive statistic was performed and the results indicated that they were lack of knowledge about genetics topic. Most of students were not familiar to genetic terms, for example locus, missense mutation, nonsense mutation, frameshift mutation, and karyotype. Students were not comfortable to use OMIM and draw pedigree. Respondents argued that more education strategy could be applied to improve student knowledge and understanding of the genetics.Conclusion: Introduction and recognition of genetics topic in nursing education was needed. Integration of genetics topic into nursing education can be applied by the existing subject or by itself subject to students; either individually or classically.